The participation of Yakub Hoffman in the organization of the circle for raising the cultural level of the village at the Kremenets Lyceum - Yaremchuk, Valentyna (Ukrainian Peasant, 2024)
The purpose of the study: to reveal the participation of Yakub Hoffman, an ambassador to the Polish Sejm, in the organization of a circle for raising the cultural level of the village at the Kremenets Lyceum (1937), to highlight his activities in the socio-political field and his views on peasantry. The scientific novelty of the publication lies in the fact that for the first time the following sources were considered and introduced into scientific circulation: archival documents of the activity project of the circle; correspondence with Stefan Charnotsky curator of the Kremenets Lyceum; excerpts from shorthand notes of the ambassador’s speeches. The methodological basis of the article is the principle of historicism, systematicity and objectivity. When presenting the material, a problem-chronological approach was used. Special attention is paid to the methodology of working with archival sources. Based on the results of the developed source base, the general picture of functioning the circle was reproduced. The article mentions the availability of primary and secondary project documents. The analysis of these documents revealed the participation of Ya. Hoffman in its implementation. Conclusions. Yakub Hoffman’s professionalism as an educator was manifested in his ambassadorial activities. He understood that the policy of the government should be fair so as not to be exposed to the resistance of national minorities, the largest percentage of which was the rural population. During the sessions of the Seim, Ya. Hoffman emphasized the importance of the education of peasantry. He took an active part in the educational program: initiated the creation of an educational group in the parliament; participated in writing the project of the organization of the circle for raising the cultural level of the village, the activity of which was implemented at the Kremenets Lyceum. The following components were prescribed in the program for the creation of the circle: determining of the goal, tasks; methodological guidelines for collecting and processing observations, delivering lectures, organizing seminars; load selection, which included 12 subjects; proposals regarding the teaching staff. The views of Ya. Hoffman on the role of government in the peasant issue, recorded in archival materials, are still relevant today.